Human glioblastoma stem-like cells accumulate protoporphyrin IX when subjected to exogenous 5-aminolaevulinic acid, rendering them sensitive to photodynamic treatment - Schimanski, Adrian; Etminan, Nima (Journal of photochemistry and photobiology. B, Biology, 2016)
Glioblastoma (GBM) is the most frequent and lethal primary brain tumor in adults. Despite multimodal therapy combining resection, radio- and alkylating chemotherapy, disease recurrence is universal and prognosis of patients is poor. Glioblastoma stem-like cells (GSC), which can be grown as neurospheres from primary tumors in vitro, appear to be resistant to the established therapies and are suspected to be the driving force for disease recurrence. Thus, efficacy of emerging therapies may depend on targeting GSC. 5-aminolaevulinic acid-mediated photodynamic therapy (5-ALA/PDT) is a promising therapeutic approach in GBM. It utilizes the selective accumulation of the photosensitizer protoporphyrin IX (PPIX) in GBM cells after application of 5-ALA. When exposed to laser light of 635nm wavelength, PPIX initiates a photochemical reaction resulting in the generation of reactive oxygen species, which kill the tumor cells. Whether GSC accumulate PPIX and are sensitive to 5-ALA/PDT is currently unknown. Therefore, human GSC were derived from primary tumors and grown as neurospheres under serum free conditions. When subjected to exogenous 5-ALA, a dose- and time-dependent accumulation of PPIX in GSC was observed by flow cytometry, which varied between individual GSC preparations. Subsequent exposure to laser light of 635nm wavelength substantially killed GSC, whereas treatment with 5-ALA or exposure to laser light only had no effect. LD50 values differed between GSC preparations, but were negatively correlated with PPIX accumulation in GSC. In summary, we report for the first time that glioblastoma stem-like cells accumulate PPIX when subjected to 5-aminolaevulinic acid and are sensitive to 5-aminolaevulinc acid based photodynamic therapy.
Gesehen am 17.07.2019
Available online 27 August 2016